Influence of family size on the relationship of blood pressure with arms, neck and wrist circumferences in the female students of Rajshahi University, Bangladesh (University Journal of Zoology, Rajshahi University, 2007)
Key words: Body mass index; waist circumference; blood pressure; age Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 33-39